Shariah Business Law's Perspectives on the Use of Chemical Preservatives in the Salted Fish Industry - Rahmah, Saidah; Andaryuni, Lilik; Ardyansah, Muhammad Rafi (Islamic Economic Law Study Program, Faculty of Sharia Sultan Aji Muhammad Idris Samarinda Islamic State University, 2024)
Abstract: This article discusses the perceptions of salted fish business actors regarding the use of chemical preservatives in terms of sharia business law. This research aims to determine the extent of knowledge about chemicals and doing business in accordance with the recommendations of the Islamic religion (Shariah). The type of research used in this research is qualitative research, using an empirical approach. The data collection techniques used were observation, interviews and documentation. And the data analysis technique is carried out in a qualitative descriptive manner, namely describing, explaining and analyzing the results of the research that has been carried out. The results of this research explain the procedures or behavior of business actors in processing salted fish, namely by cleaning the inside of the fish's stomach and washing it with clean water, then soaking it in a container containing salt water for approximately 12 hours, then washing the fish. which has been previously soaked in clean water, as for the use of additional materials such as preservatives, business actors usually do this only during emergency situations, such as when sending out of town over long distances, preservatives are sprayed on the outside of the fish or the cardboard in which the fish is stored to avoid growth. bacteria that can damage the fish, as for doing business in accordance with the recommendations of the Islamic religion (Shariah), business people still don't really understand this, this is because of limited educational background and minimal knowledge about ethics and appropriate business methods. with Sharia Business Law, so that behavior is still found that is not in accordance with Sharia in business practices, there is even a lack of clarity regarding the correct information for making a profit, so things like that are not recommended in sharia business.